The Impact of Security Orchestration, Automation, and Response (SOAR) on Security Operations Center (SOC) Efficiency: A Comprehensive Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Security Operations Centers (SOCs) are the backbone of an organization's cybersecurity defense, responsible for monitoring security events, detecting and investigating incidents, and responding to attacks. However, SOC teams often need help with the challenge of being overwhelmed with alerts and incidents, making it difficult to keep pace with the evolving threat landscape. This can lead to delayed incident response times, increased risk of compromise, and a weakened overallsecurity posture.Security Orchestration, Automation, and Response (SOAR) have emerged as promising technology to help SOC teams enhance their efficiency and effectiveness. SOAR platforms offer the capability to automate tasks, streamline workflows, and provide a single pane of glass for managing security operations. This can enable SOC teams to reduce their workload, improve their response times, and make better decisions.